Foliar Applied Acetylsalicylic Acid Induced Growth and Key-Biochemical Changes in Chickpea (Cicer arietinum L.) Under Drought Stress - Iqbal Hussain; Rizwan Rasheed; Muhammad Arslan Ashraf; Muhammad Mohsin; Syed Muhammad Ali Shah; Dr Abid Rashid; Muhammad Akram; Jaweria Nisar; Muhammad Riaz (SAGE Publishing, 2020)
The exogenous application of acetylsalicylic acid (ASA) is stated to increase tolerance of plants against different environmental stresses. Therefore, the present study was planned to get insight into ASA-mediated regulation of growth, secondary metabolism, and oxidative defense in 2 chickpea varieties. Ten seeds of 2 chickpea varieties (DG-89 and Bittle-98) were sown in plastic pots containing sandy loam soil with 3 drought stress levels, i.e. wet conditions or flooded water (100% FC) as recommended control, 75% FC, 50% FC and 25% FC for chickpea. The moisture contents were maintained and regularly monitored through the addition of normal irrigation water. The design of experimental was completely randomized with 3 replicates per treatment. Penultimate leaves were harvested with knife after 20 days of foliar spray to observe the effect of exogenously applied ASA (100 mg/L) on growth, and key-biochemical attributes of chickpea plants (DG-89 and Bittle-98) under drought stress regimes. Drought stress regimes caused a substantial decline in shoot (37% and 35%) and root length (67% and 78%), shoot (80% and 76%) and root (62% and 68%) fresh masses, shoot (71% and 63%) and root (77% and 74%) dry masses, leaf area per plant (77% and 80%), chlorophyll a (7% and 45%), chlorophyll b (57% and 42%), total chlorophyll (30% and 39%), total carotenoids (76% and 54%), total anthocyanins (38%), reducing sugar (10% and 57%), total soluble proteins (77% and 44%), total flavonoids (61% and 59%) and total phenolics (58% and 31%) contents in both DG-89 and Bittle-98, respectively. A significant increase in MDA (25%), H 2 O 2 contents (100% and 62%), proline (145% and 131%), and ascorbic acid (133% and 203%) contents was documented in stressed plants of both varieties, respectively. Additionally, drought stress significantly improved the activities of POD (154% and 76%), CAT (87% and 45%) and SOD (248% and 143%) in both varieties. Exogenous application of ASA reduced drought-mediated oxidative stress by reducing MDA (53% and 14%), and H 2 O 2 (84% and 56%) contents, proline contents (50% and 17%) and enhanced the shoot (6% and 25%) and root (43% and 33%) dry masses, leaf area (9% and 10%), chlorophyll a (7% and 32%), b (82% and 81%), and carotenoids (53% and 33%) in both barley cultivars. When plants of chickpea was treated with ASA had greater total anthocyanins (26% and 35%), free amino acids (48% and 28%), ascorbic acid contents (135% and 179%), total soluble proteins (34% and 23%), total flavonoids (58% and 35%) and phenolic (50% and 69%)contents besides the POD (41% and 64%), CAT (23% and 56%) and SOD (73% and 72%) enzymes activities. Plants of DG-89 showed more tolerance to drought stress than that of Bittle-98 as a manifest from higher plant biomasses. Thus, our results showed that foliar-applied ASA is an effective strategy that can be used to improve the tolerance of chickpea plants to drought stress.